Assessment of extra pulmonary tuberculosis (EPTB) cases from selected tuberculosis units (TUs) of Himachal Pradesh, India - Bhardwaj, Ashok Kumar; Kumar, Dinesh; Raina, Sunil Kumar; Sharma, Sushant; Chander, Vishav (International Journal of Health, 2015)
Introduction: Extra-Pulmonary Tuberculosis (EPTB) gained attention for study its local disease epidemiology for disease control.Objective: To study the distribution and determinants of EPTB in randomly selected tuberculosis units (TUs) of Himachal Pradesh. Methodology: Multistage random sampling was used; four districts were selected randomly from total 12 districts of state and then one TU was selected from each selected district. In addition, two medical colleges were also included as a referral point for EPTB cases. Â Results: Total 463 EPTB cases were studied during one-year study period; pleural (41.9%) and Lymph Node (31.3%) was frequently observed involved sites. Among male's pleural effusion (48.2%) was commonly involved site followed by lymph node (23.5%), whereas, lymph node was involved in 40.6% followed by pleural effusion in 34.4% females. Other common sites for EPTB were abdomen (6.0%), bone (5.6%), meninges (5.2%) and pericardium (3.9%) and for both males and females. Mean duration of diagnosis since appearance of symptoms was 40 days; only 10.0% of patients received antibiotics for the average of two weeks before formulating EPTB diagnosis. About 35.0% patients underwent FNAC (Fine Needle Aspiration Cytology) to establish diagnosis.Conclusion: Invasive diagnostic facilities at peripheral health institutions will help further to better understand EPTB epidemiology.